Analysis of mathematical literacy through pull out photo math box based on augmented reality technology in deaf students - Naila Nafisatun Mu'alamah; Nila Ubaidah (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze mathematical literacy through the Pull-Out Photo Math Box based on augmented reality technology in deaf students. The approach used in this study is a qualitative descriptive approach. The research subjects consist of eight deaf students in grade IV at SLB Negeri Semarang, with three students representing different levels of mathematical literacy. The subjects were selected using purposive sampling. Data were collected through mathematical literacy tests, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results show that mathematics learning on plane figures through the Pull-Out Photo Math Box based on augmented reality technology enhances students' mathematical literacy. High-category students are able to meet three indicators of mathematical literacy, medium-category students meet two indicators, while low-category students meet only one indicator. Additionally, all students across the high, medium, and low categories found that learning using the Pull-Out Photo Math Box based on augmented reality technology was an engaging and useful visual medium for understanding plane figures. This study contributes to the field of mathematics education by demonstrating the effectiveness of augmented reality-based learning tools in improving mathematical literacy among deaf students. The findings highlight the potential of innovative visual media in making mathematical concepts more accessible and engaging for students with special needs.